Phytochemical Analysis of Silver Nanoparticles of Zingiber officinale and Evaluation for Its Antibacterial Property - Krishna Goutham; Brahma Neha; Alex Arockia (Wolters Kluwer Medknow Publications, 2024)
Nonessential heavy metals are toxic to human health. In this study, mercury, a hazardous metal, was detected by colorimetric analysis using Zingiber (Z.) officinale. The eco-friendliness of this method was also emphasized. The ultraviolet (UV) spectrum is a broad peak observed at 200-250 nm in Z. officinale leaf extracts. The UV spectrum of green synthesized Z. officinale exhibited an absorption band of 286 nm, which confirms the nanoparticle (NP) synthesis. Fourier transform infrared (FTIR) analysis of the vibrational peak around 3307 cm−1 is assigned to ν(O-H) stretching that could possibly emanate from carbohydrates or phenolics. The peaks found around 2917 and 2849 cm−1 are ascribed to the -C-H stretch of the alkyl group, and the peak around 1625 cm−1 is due to the enolic β-diketones or -C = O stretch of carboxylic acids, while the corresponding -C-O stretch is observed around 1375 and 1029 cm−1. The assignment of peaks is similar. It is clear from the scanning electron microscope (SEM) image that the constituent parts were nonuniform, sphere-shaped, agglomerated, and of an average size of 30.9 nm. X-ray diffraction (XRD) analysis was used to determine the structural characteristics and crystalline nature of Z. officinale. The observed intensity peaks at 32.35°, 36.69°, 39.24°, 44.76°, 59.42°, and 67.35° are, respectively, of the Z. officinale diffraction 2θ values, which correspond to the standard database values. The synthesized copper NPs synthesized tested antibacterial properties against various strains of microorganisms, including Escherichia coli: 25 μg/mL 2.01 ± 0.11 and 100 μg/mL 5.37 ± 0.12, Staphylococcus (S.) aureus: 25 μg/mL 1.05 ± 0.71 and 100 μg/mL 11.43 ± 1.27, Streptococcus mutans: 25 μg/mL 02.01 ± 0.1 and 100 μg/mL 15.67 ± 0.17, and Enterococcus faecalis: 25 μg/mL 03.11 ± 0.7 and 100 μg/mL 18.32 ± 0.2. The short novelty of Z. officinale lies in its potential relevance to human health, as it has been found to possess bioactive compounds with various medicinal properties, such as antimicrobial, antioxidant, and anti-inflammatory activities, making it a promising natural resource for therapeutic applications.